Factors relating to nonpublication and publication bias in clinical trials in Canada: A qualitative interview study. Issue 3 (9th November 2022) - Morrow, Richard L.; Mintzes, Barbara; Gray, Garry; Law, Michael R.; Garrison, Scott; Dormuth, Colin R.
Abstract : Aims: This study aims to understand factors contributing to nonpublication and publication bias in clinical trials in Canada. Methods: Qualitative interviews were conducted between March 2019 and April 2021 with 34 participants from the Canadian provinces of Alberta, British Columbia and Ontario, including 17 clinical trial investigators, 1 clinical research coordinator, 3 research administrators, 3 research ethics board members and 10 clinical trial participants. We conducted a thematic analysis involving coding of interview transcripts and memo‐writing to identify key themes. Results: Several factors contribute to nonpublication and publication bias in clinical trial research. A core theme was that reporting practices are shaped by incentives within the research system taht favour publication of positive over negative trials. Investigators are discouraged from reporting by experiences or perceptions of difficulty in publishing negative findings but rewarded for publishing positive findings in various ways. Trial investigators more strongly associated positive clinical trials than negative trials with opportunities for industry and nonindustry funding and with academic promotion, bonuses and recognition. Research institutions and ethics boards tended to lack well‐resourced, proactive policies and practices to ensure trial findings are reported in registries or journals. Conclusion: Clinical trial reporting practices in Canada are shaped by incentives favouring reporting of positive over negative trials, such as funding opportunities and academic promotion, bonuses and recognition. Research institutions could help change incentives by adopting performance metrics that emphasize full reporting of results in journals or registries.